Manganese Superoxide Dismutase (SOD2) Gene Val16Ala polymorphism in type 2 diabetic patients - Muriki Naresh Kumar; Anil Kumar; Pallavi Anand (Al Ameen Medical College, 2020)
Background: Reactive oxygen species generated by hyperglycemia modify structure and function of lipids, proteins and other molecules taking part in chronic vascular changes in diabetes mellitus (DM). In patients with DM low activity of scavenger enzymes has been observed. Within mitochondria, the main defence against oxidative stress is provided by Manganese superoxide dismutase (Mn SOD). Val16Ala may be a single nucleotide polymorphism (SNP) within the Mn SOD gene, predicted to affect intra-mitochondrial transport of the enzyme. Functional polymorphisms of these antioxidant enzyme are reported to be involved in pathogenesis of T2DM individuals. Low activity of scavenger enzymes may be deteriorated by oxidative stress. This study was undertaken to investigate the association between SOD2 gene polymorphisms and Total Antioxidant capacity of T2DM. Objective: To find the V16A polymorphism of Manganese superoxide dismutase (SOD2) and its association with Total antioxidant capacity in Type 2 Diabetic patients. Methods: We assessed SOD2 gene V16A polymorphism, Total Antioxidant Capacity (TAC) and Lipid Profile in 100 patients of type 2 diabetes Mellitus and 100 healthy controls. This study was conducted in Rama Medical College, Hospital & Research centre, Kanpur. Statistical analysis was done by chi-square test and student t test. Result: Significant differences in allele and genotype distribution among T2DM and control persons were found in SOD2 genes. Serum TAC levels was significantly decreased in T2DM subjects compared to the control group. TAC was higher in CC than in TT and CT genotype of SOD2 gene. Conclusion: the results of our study demonstrate that oxidative stress in DM can be accelerated not only due to increased production of ROS caused by hyperglycemia but also by reduced ability of antioxidant defense system caused at least partly by SNPs of SOD2.